2022
DOI: 10.1186/s12936-022-04160-3
|View full text |Cite
|
Sign up to set email alerts
|

Incremental cost and cost-effectiveness of the addition of indoor residual spraying with pirimiphos-methyl in sub-Saharan Africa versus standard malaria control: results of data collection and analysis in the Next Generation Indoor Residual Sprays (NgenIRS) project, an economic-evaluation

Abstract: Background Malaria is a major cause of morbidity and mortality globally, especially in sub-Saharan Africa. Widespread resistance to pyrethroids threatens the gains achieved by vector control. To counter resistance to pyrethroids, third-generation indoor residual spraying (3GIRS) products have been developed. This study details the results of a multi-country cost and cost-effectiveness analysis of indoor residual spraying (IRS) programmes using Actellic®300CS, a 3GIRS product with pirimiphos-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
0
5
0
Order By: Relevance
“… ‣ Highly effective against malaria ( WHO, 2019b ), dengue ( Vazquez-Prokopec et al, 2017 ) and visceral leishmaniasis ( Rijal et al, 2019 ); may also be effective against peridomestic cutaneous leishmaniasis ( González et al, 2015 ). ‣ Cost per person per year: US$5.33 in Africa ( Yukich et al, 2022 ). ‣ Must be applied by a trained person ( Malaria Consortium, 2021 ; Sadasivaiah et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“… ‣ Highly effective against malaria ( WHO, 2019b ), dengue ( Vazquez-Prokopec et al, 2017 ) and visceral leishmaniasis ( Rijal et al, 2019 ); may also be effective against peridomestic cutaneous leishmaniasis ( González et al, 2015 ). ‣ Cost per person per year: US$5.33 in Africa ( Yukich et al, 2022 ). ‣ Must be applied by a trained person ( Malaria Consortium, 2021 ; Sadasivaiah et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that, compared with LLINs, IRS was about five times more expensive per person protected per year. This means that IRS is considerably less cost-effective than expected [2,45,46]. Factors related to vector behaviour were not explicitly considered in this study but were clearly highlighted in Benin [11].…”
Section: Limited Protection Of Long-lasting Insecticide-treated Nets ...mentioning
confidence: 92%
“…Compared to LLINs alone, IRS alone and LLINs + IRS seemed more efficient but IRS has limitations concerning cost and budgets. Logistics, domestic contribution, and monitoring are also difficult to manage [45]. The local applicators of insecticides frequently divert products for selling to private use in fields for growing food and other industrial crops.…”
Section: Limited Protection Of Long-lasting Insecticide-treated Nets ...mentioning
confidence: 99%
“…Mosha et al 2023;Protopopoff et al 2018). This has resulted in some countries stopping their IRS programs, partly due to cost considerations, even though IRS remains highly cost effective (Oxborough 2016;Yukich et al 2022). However, IRS has several advantages which might be useful if the costs of IRS could be reduced.…”
Section: Introductionmentioning
confidence: 99%